The challenges of a youth and adult education policy (Revista Contexto & Educação, 2023)
This article aims to analyze documents of a public education policy and its contributions to educational practices oriented to Youth and Adult Education (EJA). In this regard, the Municipal Education Plan of the municipality of Conde, state of Paraíba, and the reports of the General Coordination of the EJA constitute analyzers of documentary research. It presents, methodologically, the following analytical axes: a) the emergence of the municipal plan and its relationship with adult education; b) characteristics and initiatives of the municipal network; and c) actions and strategies of permanence of students. There are indicators, in the reports, despite the limits, that direct to a "horizontality" of educational practices in the provision of education of youth and adults.